PEMBINAAN KEAGAMAAN LANJUT USIA DI PANTI SOSIAL TRESNA WERDA KHUSNUL KHOTIMAH PEKANBARU RIAU - Silawati Silawati (Lembaga penelitian dan pengabdian kepada masyrakat, 2011)
One of phenomenon which adequately pulls deep its nation-building problem far advanced in years (lansia). lansia's population at Indonesian tending worked up continually which is 6,9% (1990), 7,18% (2000), predict 9,77% (2010), and 11,34% (2020) (BPS: 1998). It logical consequence, necessary well-being service step-up for old age at various area as social as, health, keagamaan's education and construction. Base Commanding regulation No. 43 Years 2004 about well-being Increasing Effort Performings far advanced in years Sections 1, that lansia the so called is someone already reach age 60 years onto. As follow-up of that Mensos's decision, at arranges Social Service Guidance Far Advanced In Years at Panti (No.. 4 / PRS 3 / KPTS / 2007) one that meaty about construction pattern / leadings for far advanced in years at panti social. There is pattern even construction / intended leading deep that guidance as guidance of spiritual's mental and spirituality by use of discourse method, demonstration and discussion, religious service guidance everyday, pengajian, read al-quran. Result observationaling to show that religion construction at Panti this Social, we give construction as discourse of religion, spirituality guidance, manner, moral, and another dogma. There are many sometimes clients a new one comes here not know ridicule which makes the point sholat, get ablution, etc.. Nah that is task we in here, from them that don't know whatever good it good sholat procedure, get ablution that really, until they can and know it with every consideration and truth. Now they have known it and understands ridicule which sholat's procedure, get ablution’ and another religion fomentation with every consideration and truth. At while do keagamaan's construction officer divides clients available one come under into individual and group.